A tale of two countries: the sociopolitical integration of Latino immigrants in Spain and in the United States - Perez-Nievas, S; Cordero, G; Mallet-Garcia, ML (SAGE Publications, 2021)

(untitled)
This special issue addresses the need for cross-national analyses on immigrant integration. The articles in this issue examine the integration processes of Latino immigrants in the United States and in Spain in several aspects—socioeconomic, legal, educational, and political—and through varied methods—quantitative as well as qualitative—contributing to the literature in several ways. By focusing on the same ethnic group across different contexts, it provides a thorough comparison of the mechanisms at play in their integration processes. It emphasizes the context-specific and culture-specific elements that most affect immigrants’ integration. This special issue gathers nine articles that offer complementary perspectives on the integration of Latino immigrants in Spain and the United States.